Pengaruh Model Pembelajaran Numbered Heads Together Terhadap Keaktifan Belajar Siswa - Daulay, Irma Sari; Harahap, Rani Astria Silvera; Harahap, Doarni (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Education is an important thing in human life, especially in modern times education is a primary need for humans. The aim of this research is to find out whether there is an influence of the number head together learning model on students' active learning. This research is using experimental method. Data collection techniques in this research were obtained through observation, documentation and tests. And the data analysis technique in this research uses the normality test and homogeneity test, which is then carried out by hypothesis testing. The results of hypothesis testing using the t test showed that the t value was 29.5 when compared with t table at a significance level of 5% or 0.05 with degrees of freedom (dk) = 28 which was 2.04. Based on these data, tcount is greater than ttable or (29.5 > 2.04), so Ha is accepted and Ho is rejected. So it can be concluded that there is a significant influence of the Numbered Heads Together (NHT) learning model on the active learning of class V students at SD Negeri 1001 Batang Bulu